2006
DOI: 10.1016/j.ultsonch.2005.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of ultrasonic extraction of extractive substances from garden (Salvia officinalis L.) and glutinous (Salvia glutinosa L.) sage

Abstract: The kinetics of ultrasonic extraction of extractive substances (ES) from dry herbs of garden (Salvia officinalis L.) and glutinous (Salvia glutinosa L.) sage using petroleum ether, 70% ethanol or water at 40 degrees C, as well as the composition of dry extracts, were studied. The mechanism of ultrasonic extraction is confirmed to occur in two steps: first, dissolution of the ES near the particle surface (washing) and, second, diffusion from the solid particles to the bulk of the liquid extract (slow extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(64 citation statements)
references
References 11 publications
1
57
0
6
Order By: Relevance
“…When extraction process was performed in 2 % sage loading at different temperatures, the concentration of TSS corresponded with the extract yield of 17.73 and 24.99 g/ 100 g contained 6.04-8.31 g/100 g TPC and 4.13-6.77 g/ 100 g TFC. Velickovic et al (2006) studied two different Salvia species with different solvents and they reported 28.0 % aqueous extract yield from Salvia officinalis and 34.4 % from S. glutinosa at 80°C. Durling et al (2007) extracted S. officinalis with 81 % methanol and they found that extract yield and recovery of bioactive components of S. officinalis increased by increasing temperature due to higher solubility and diffusion coefficient.…”
Section: Effect Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…When extraction process was performed in 2 % sage loading at different temperatures, the concentration of TSS corresponded with the extract yield of 17.73 and 24.99 g/ 100 g contained 6.04-8.31 g/100 g TPC and 4.13-6.77 g/ 100 g TFC. Velickovic et al (2006) studied two different Salvia species with different solvents and they reported 28.0 % aqueous extract yield from Salvia officinalis and 34.4 % from S. glutinosa at 80°C. Durling et al (2007) extracted S. officinalis with 81 % methanol and they found that extract yield and recovery of bioactive components of S. officinalis increased by increasing temperature due to higher solubility and diffusion coefficient.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…It is generally reported that extraction rate increases with increasing in temperature and solid/liquid ratio, and decreasing the particle size. Earlier works reported extraction efficiency in different sage species by using different extraction methods, such as; conventional (Schneider et al 2011), pressurized liquid (Hossain et al 2010), ultrasonic assisted, (Velickovic et al 2006;Velickovic et al 2008), supercritical CO 2 (Aleksovski and Sovova 2007;Glisic et al 2010) and ultrasonic assisted-supercritical CO 2 combination (Glisic et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[6] It has also been established that UAE is more effective than classical maceration-CM (shorter time, larger output of volatile constituent extraction). [7] UAE allows extraction at a lower temperature of the process, which is significant for raw materials that possess easily degradable ingredients. [8] Essential oils are accumulated by plants in specialized secretory structures, the destruction of which is one of the stages for their release.…”
Section: Introductionmentioning
confidence: 99%
“…29 The kinetic models for UAE of natural products are usually adapted from those for conventional solid-liquid extraction or leaching, a well-known mass transfer process in chemical engineering. Several simplified empirical models have been developed for describing the extraction kinetics of natural products from plant materials in various mathematical forms, parabolic, hyperbolic, power-law and exponential.…”
Section: Uae Process Kineticsmentioning
confidence: 99%